AMS 설문지 검사를 이용한 성기능 장애 환자의 腎氣丸 투여 10례에 대한 임상보고 - 신선미(Seon Mi Shin); 고흥(Heung Ko); 김기태(Gi Tea Kim); 김호현(Ho Hyun Kim); 박선영(Sun Young Park) (동의생리병리학회지, 2014)
The purpose of this study was to investigate the clinical results of the 10 male climateric syndrome cases while treated with Singi-hwan. All patients were treated with Singi-hwan two times a days for 5 weeks. We checked testosterone, PSA in blood, HRV and AMS questionnaire score. The questionnaire score was improved after taking Singi-hwan. Stress resistance and autonomic nervous system activity is increased, but there was no statistical significance except for ApEn. Taking Singi-hwan did not affect the serum concentration of testosterone, PSA and blood biochemical tests. The next placebo-controlled studies about late onset hypogonadism treated with Singi-hwan are needed. KCI Citation Count: 1